PROBLEMS AND SOLUTIONS IN PROVIDING GEOINFORMATION OF THE STATE LAND CADASTRE - Khakimova Kamola Rakhimjonovna; Gofurov Khalimjon Vokhidjon ogli (Western European Studies, 2024)
This article is devoted to the existing problems in the provision of the state land cadastre with geoinformation technologies and the issues of offering solutions to them. The article analyzes modern approaches to effective management of land resources through the digitization of the land Cadastre and the introduction of geoinformation systems. It also shows the importance of updating the technological infrastructure of the cadastral system, training of personnel, and public-private sector cooperation. The results and recommendations of the study determine the main directions for improving the effectiveness of land resource management in the country and the transition to a digital economy.
Keywords: land cadastre; geoinformation technologies; digitization